A ghostly undertaking - Kappes, Tonya (Ghostly Southern mystery, 2013)
"Bopped on the head from a falling plastic Santa, local undertaker Emma Lee Raines is told she's suffering from 'funeral trauma'. It's trauma all right, because the not-so-dearly departed keep talking to her. Take Ruthie Sue Payne--innkeeper, gossip queen, and arch-nemesis of Emma Lee's granny--she's adamant that she didn't just fall down those stairs. She was pushed. Ruthie has no idea who wanted her pushing up daisies. All she knows is that she can't cross over until the matter is laid to eternal rest. In the land of the living, Emma Lee's high-school crush, Sheriff Jack Henry Ross, isn't ready to rule out foul play. Granny Raines, the widow of Ruthie's ex-husband and co-owner of the Sleepy Hollow Inn, is the prime suspect. Now Emma Lee is stuck playing detective or risk being haunted forever, "--Page 4 of cover.